EFCAB13 is a Novel Age-Dependent Promotor of SOCE in Blood Platelets and Megakaryoblastic MEG-01 Cells - Redondo, Pedro C.; Granados, María P.; Fernández, Esperanza; Collado-Pérez, Miguel-A; Teruel-Montoya, Raúl; Ferrer-Marín, Francisca; Berna-Erro, Alejandro (Thrombosis and Haemostasis, 2025)
Intracellular Ca2+ homeostasis is essential to regulate the molecular mechanisms underlying platelet physiology and aggregation. Store-operated Ca2+ entry (SOCE) is the main mechanism of extracellular Ca2+ influx in platelets and it has been involved in platelet aggregation.We reported the function of the uncharacterized protein EFCAB13 as a positive regulator of SOCE in megakaryoblastic cells and platelets from either mothers and their newborns. Alternatively, MEG-01 and HEK293 cells were used as sourrogated of platelets to perform changes in the expression of EFCAB13, which was ensured by immunoprecipitations and Western Blotting techniques. Once EFCAB13 was genetically modifies and to achive its role in Ca2+ homeostasis we used fluorescence microscope under single cells configuration. Finally, MEG-01 maturation was assay using flow-cytometry and specific fluorescent antibodies or cell cycle dies. Intracellular distribution and protein interaction was also evaluated by confocal microscopy.EFCAB13 is underexpressed in neonatal platelets as compared with adults, indicating an age-dependent expression. Silencing of EFCAB13 expression reduced the colocalization of STIM1 with Orai1 and, subsequently, impairs SOCE in megakaryoblastic MEG-01 cells stimulated with thapsigargin (TG). Coimmunoprecipitation experiments showed that EFCAB13 interacts with Orai1, and colocalization between both proteins increases during TG-evoked SOCE. Indeed, EFCAB13 localized nearby the ER during TG-evoked SOCE activation. Finally, PMA-induced MEG-01 maturation was altered in EFCAB13-silenced cells.Altogether, we conclude that EFCAB13 binds to Orai1 to stabilize and regulate the STIM1/Orai1 complex formation, which is necessary to support SOCE in adults. However, its function is less important in neonatal platelets. This regulatory function may also be important for megakaryocytic physiology during maturation. Therefore, EFCAB13 could be an interesting target for specific treatment of maternal hemostatic disorders during pregnancy.
Keywords: EFCAB13; STIM1; Orai1; SOCE; platelets